Immune response to COVID-19 mRNA vaccination in previous nonresponder kidney transplant recipients after short-term withdrawal of mycophenolic acid 1 and 3 months after an additional vaccine dose - Kühn, Tessa; Speer, Claudius; Morath, Christian; Bartenschlager, Marie; Kim, Heeyoung; Beimler, Jörg; Buylaert, Mirabel; Nußhag, Christian; Kälble, Florian; Reineke, Marvin; Töllner, Maximilian; Klein, Katrin; et al. (Transplantation, 2023)
Background. - The impaired immune response to coronavirus disease 2019 (COVID-19) vaccination in kidney transplant recipients (KTRs) leads to an urgent need for adapted immunization strategies. Methods. - Sixty-nine KTRs without seroconversion after ≥3 COVID-19 vaccinations were enrolled, and humoral response was determined after an additional full-dose mRNA-1273 vaccination by measuring severe acute respiratory syndrome coronavirus 2-specific antibodies and neutralizing antibody activity against the Delta and Omicron variants 1 and 3 mo postvaccination. T-cell response was analyzed 3 mo postvaccination by assessing interferon-γ release. Mycophenolic acid (MPA) was withdrawn in 41 KTRs 1 wk before until 4 wk after vaccination to evaluate effects on immunogenicity. Graft function, changes in donor-specific anti-HLA antibodies, and donor-derived cell-free DNA were monitored in KTRs undergoing MPA withdrawal. - Results. - Humoral response to vaccination was significantly stronger in KTRs undergoing MPA withdrawal 1 mo postvaccination; however, overall waning humoral immunity was noted in all KTRs 3 mo after vaccination. Higher anti-S1 immunoglobulin G levels correlated with better neutralizing antibody activity against the Delta and Omicron variants, whereas no significant association was detected between T-cell response and neutralizing antibody activity. No rejection occurred during study, and graft function remained stable in KTRs undergoing MPA withdrawal. In 22 KTRs with Omicron variant breakthrough infections, neutralizing antibody activity was better against severe acute respiratory syndrome coronavirus 2 wild-type and the Delta variants than against the Omicron variant. - Conclusions. - MPA withdrawal to improve vaccine responsiveness should be critically evaluated because withdrawing MPA may be associated with enhanced alloimmune response, and the initial effect of enhanced seroconversion rates in KTRs with MPA withdrawal disappears 3 mo after vaccination. Export
Gesehen am 04.08.2023